Functional Nucleic Acid Based Biosensors for Food Safety Detection - Luo, Yunbo (Springer Singapore, 2018)
This book highlights the development of a functional nucleic acid based biosensor detection method in the context of food safety. Although there have been major advances in food processing technology in both developed and developing countries, food safety assurance systems are generally becoming more stringent, in response to growing (both real and perceived) food safety problems. These problems are due in part to foodborne microorganisms, heavy metals, and small chemical molecules (biological toxins, pesticide residues, and veterinary drug residues), etc. In addition, the nucleic acid biomarkers (DNA methylation, microRNA, and circRNA) induced by these risk factors are also closely related to food safety. Accordingly, this book offers a brief guide to targets and strategies in functional nucleic acid based biosensors for food safety detection. Divided into several chapters that focus on various respective targets, it will be a valuable resource for students and researchers in the fields of biosensor detection, food science etc.